Analisis Perhitungan Kebutuhan Tenaga Kerja di Bagian Pendaftaran Rawat Jalan Rawat Jalan dengan Menggunakan Metode Full Time Equivalent (FTE) di BBKPM Surakarta Periode Tahun 2019-2020 - Kustanti; Setia Hari Nurjannah; Bangkit Ary Pratama (Indonesian Journal on Medical Science, 2023)
Achieving good productivity requires a balance between workload and the workers' abilities. Maintaining this balance between productivity and workload is done by providing healthcare services according to standards. Workloads that do not meet the standards can result in poor service. The research aims to determine the workforce needs in the registration department using the FTE method at the Balai Besar Kesehatan Paru Surakarta in 2019-2020. The sample for this study used accidental sampling technique, while the method to determine the number of observations used The Maytage Company method, and this research adopts a retrospective approach.The research findings show that the workload in the registration department for outpatient services is 8,705 patients. Based on the standard patient service time of 10 minutes, the target workload per hour in the registration department at BBKPM Surakarta is to serve 6 patients. With an effective work time of 7 hours per day and 5 working days per week, the effective work time in the registration department for outpatient services is 1,680 hours per year. Using the FTE formula above, it is determined that 1 registration officer is needed at BBKPM Surakarta. In conclusion, the calculation of workforce needs using the FTE method indicates that BBKPM Surakarta does not require additional registration officers for outpatient services. Based on the analysis of workload and target work time per hour, it is calculated that the current workforce is sufficient to efficiently serve patients.